Pembelajaran Paduan Suara Pada Lagu Dek Sangke Di Kegiatan Ekstrakurikuler SMP Negeri 3 Palembang - Yunisa Yunisa; A. Heryanto; Nofroza Yelli (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This research is motivated by the formulation of the problem raised in this research, namely choral learning in the songdek sangke in extracurricular activities at SMP Negeri 3 Palembang. The purpose of this research is to find out and describe the process of learning choirs in the song Deck Sangke in extracurricular activities at SMP Negeri 3 Palembang. The method used is descriptive qualitative with data collection techniques using triangulation from three data sources, namely, observation, interviews and documentation. The results of the research show that choir learning in this extracurricular activity goes well and is in accordance with the applicable curriculum and in accordance with the learning plans that have been prepared. The process of learning the choir on the song Deck Sangke in extracurricular activities at SMP Negeri 3 Palembang makes it easier for participants who take part in extracurricular activities to understand the material so that learning objectives are achieved well. At the end of the lesson, the trainer gave a test/task, namely singing the regional songdek sangke in groups with a predetermined distribution of voices, and the results were that almost all students got very good grades.